Implementasi Discovery Protocol pada Smart Home Menggunakan Media Komunikasi Bluetooth Low Energy - Rahmanda Nur Sidik; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Internet of Things (IoT) is a wireless network technology that has changed our world significantly and has become a part of the technology industry which is very important at this time, involving interconnected devices and sharing all types of data with each other that can be controlled using the Internet or other communication media such as Bluetooth. This research utilizes Universal Plug and Play (UPnP) and Bluetooth Low Energy (BLE) using the ESP32 module because it is suitable to be applied to an IoT-based smart home environment. The first reason is that BLE has advantages over other wireless technologies such as Wi-Fi, ZigBee, and Bluetooth Classic. The advantages possessed by BLE include easy configuration, fast data transmission method, wide signal coverage distance, and does not consume relatively large amounts of power. For network protocols using UPnP which is useful for connecting devices functionally. UPnP's discovery protocol method is Simple Service Discovery Protocol (SSDP), when a device enters the SSDP network, it allows the device to advertise to network control points. The control point or master on the network can scan and receive data from the intended advertising device. By customizing UPnP and BLE using the ESP32 module we can implement a system discovery that is for effectiveness on IoT in a smart home environment. The results obtained in this study are quite good with the success rate of BLE discovery performance of 100% and the processing time to connect between devices with an average of only 4 seconds..